Design, Synthesis and Anti-Influenza Virus Activity of 4-Tert-Butyl-N-(3-Oxo-1-Thia-4-Azaspiro[4.5]Dec-4-yl)Benzamide Derivatives That Target Hemagglutinin-Mediated Fusion - Cinar, Gozde; Alikadioglu, Zeynep; Soylu-Eter, Ozge; Naesens, Lieve; Cihan-Ustundag, Gokce (Wiley, 2025)
Hemagglutinin (HA) is a viral glycoprotein that mediates influenza virus entry into the host cell and is considered a relevant viral target. We here report the identification of a class of 4-tert-butylphenyl-substituted spirothiazolidinones as HA-mediated fusion inhibitors with specific activity against influenza A/H3N2 virus. The novel spirocyclic compounds were achieved by using one-pot cyclocondensation method and the chemical structures were characterized by IR, H-1 NMR, C-13 NMR, and elemental analysis. Compound 2c, bearing methyl substitutions at positions 2- and 8- of the spiro ring displayed an EC50 value against influenza A/H3N2 virus of 1.3 mu M and an antiviral selectivity index of 30. The fusion-inhibiting effect of compound 2c was revealed in the polykaryon assay which is based on cell-cell fusion when influenza virus H3 HA-transfected cells are exposed to low pH. Computer-aided docking was performed to predict the possible binding pocket in the H3 HA trimer. Resistance data and in silico studies indicated that compound 2c has an overlapping binding pocket in the stem region of H3 HA with the known fusion inhibitors TBHQ and arbidol.
Keywords: antiviral; hemagglutinin; influenza virus; spirothiazolidinone; synthesis